Previsão setorial do consumo de fontes energéticas para o Brasil: um estudo a partir da proposta de integração econometria+insumo-produto - Silva, Daniel Oliveira Paiva da (2010)
The appropriate availability of energy resources is an aspect to be considered in the recovery process of the Brazilian economical growth, such fact highlighted by the widespread use of that resource n the economy, as well as on the electric energy crises in 2001, and the natural gas in the years 2004 and 2005. That said, there is a need of reasoning of decision making, or more specifically the strategic management in the supply of energy sources. In this respect, models of prediction have been shown as an important tool to help in these decision makings. Thus some predictions were made by making use of the proposal of econometry integration + product input, this latter being hybrid for the year 2005. The econometric block was employed to endogenize the family consumption and the private investment. Completing the necessary information to carry out the predictions, the scenery setting was used for it, being of Low, of Reference, and of High ones. The integration of the two blocks by the connection strategy all along with the sceneries. That enabled to make predictions which indicated that the oil and natural gas sectors, oil and coke refinement, alcohol and electricity for the High scenery will quite double their rates of consumption on the Brazilian economy from 2006 to 2015, given an average growth of 96%. For the sceneries of Reference and of Low, the results indicate an increase respectively of 45% and 13%. Comparing the results of the predictions for the years 2006 to 2008 with the data available was possible to get at a reasonable rate of accuracy in the predictions, such fact was essentially true for the Electricity sector.